Branding the MEGA lab; methods to improve science communication and citizen science engagement - Kapono, Clifford A.; Kane, Haunani H.; Burns, John H. R. (Frontiers in Environmental Science, 2023)
The MEGA Lab uses branding and marketing techniques as a complementary form of science communication to improve citizen science. Storytelling, inclusivity, personalization, digital marketing, and collaborations are key components to brand marketing. Through branding, science projects within the MEGA Lab have increased their visibility, attracted more participants, and enhanced credibility. In addition, the MEGA Lab branding can also help citizen science projects to reach a wider audience. By promoting the MEGA Lab brand through social media, outreach events, and other channels, citizen science projects can increase inclusivity by attracting more participants who are interested in contributing to scientific research. We believe that other science research programs and citizen science projects can benefit from branding as a complementary form of science communication. By improving science communication, it is proposed that targeted citizen science projects can improve their visibility, credibility, and impact. This can lead to more effective and valuable contributions to scientific research, as well as a greater understanding and appreciation of science among the general public.